African Continental Free Trade Agreement: A review of analyses of likely impacts and challenges of implementation - Mengistu Alamneh Wassie; Lukas Kornher; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2022)
African Union member states decided to establish "the African Continental Free Trade Area (AfCFTA) during the 18th meeting of 2012 at Addis Ababa, Ethiopia. The AfCFTA aims at facilitating intra-African trade and improving Africa's trading position in the global market. In this study, we critically review and discuss the empirical studies on the topic at hand in general and the modeling approaches that have been implemented in those studies in particular. The study also gives special emphasis to the modeling approaches that are widely implemented in recent trade literature such as, inter alia, GTAP, MIRAGE, MAGNET, and LINKAGE-GIDD. Concerning the potential impact, a range of studies considered here predict that the real income impact of the AfCFTA can reach up to 7 percent from the tariff, nontariff, and trade facilitation in a dynamic setting. While the range of projected intra-trade impact is about a 33 to 82 percent increase, intra-agrifood trade is expected to grow by 22 percent, and tariff revenue loss is 0.03 percent to 0.22 percent of the GDP. The findings, in general, highlight the potential impacts of policy intervention at hand are heterogeneous across regions, countries, and sectors. This paper draws several conclusions. First, tariff reduction of the AfCFTA alone can have positive impacts. However, the gains from trade facilitation and the reduction in nontariff barriers are projected to induce greater gains. Second, studies that used scenarios of total tariff reduction, trade in goods, and static models did not consider the full potential gain of the agreement. Including trade in services in a dynamic model and taking structural non-tariff barriers needs to be addressed to tap the benefits. Third, the agreement's projected impacts are sensitive to various factors. The overwhelming tariffs (100 percent) and nontariff reductions need more attention, while nontariff trade measures are increasing globally and regionalism is coupled with trade wars between developed countries. Member countries overlapping in different Regional Economic Communities may pose implementation difficulties at different levels of integration by complicating the policy coordination and external joint tariff determination. The implication of lacking informal trade data can have a significant impact; informal cross-border trade in some countries accounts for around 75 percent of GDP. In that trade women play a dominating role with over 70 percent, resulting in a significant transformative impact if successfully implemented. Finally, various factors, such as public awareness of the agreement, challenges related to a person's free mobility and capital, reconciliation of domestic policies, and related adjustment costs and inequality impacts can affect the effects predicted by current models compared to the actual effects of the outcomes of the AfCFTA over time.
Keywords: 330; Africa; continental integration; trade; nontariff barriers; agriculture